Profile of professionals involved in slaughter and meat consumers in Itabi/SE (Research, Society and Development, 2020)
The slaughtering process has been the target of criticism, and the sanity of the facilities for not providing the necessary hygiene for the slaughtering and meat storage procedure. The objective was to expose the level of knowledge of the people involved in the slaughter process and meat consumers in Itabi / SE municipality through a form with directed questions that aimed to expose the degree of knowledge of them. Of the marchers 54.0% remain in the activity due to lack of opportunity, 63.0% of the total interviewed believe that working conditions are adequate and only 36.4% do not agree with the way animals are treated during the whole process. until the slaughter. Consumers prefer meat sold at the fair (65.7%), of the total respondents 88.24% would be willing to pay a higher price for meat where the animal was slaughtered in a stress-free environment for the animal, as 80% confirmed that they reduced consumption if they learned that slaughter practices were used. The educational level directly influences the degree of knowledge about the risks of contaminated food consumption, as well as the lower the educational level the lower the precaution to the animal integrity, the whole procedure and also after slaughter in the meat handling.